2004
DOI: 10.1063/1.1758305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fe/Schottky and Fe/Al2O3 tunnel barrier contacts for electrical spin injection into GaAs

Abstract: We compare electrical spin injection from Fe films into identical GaAs-based light-emitting diodes (LEDs) using different tunnel barriers—a reverse-biased Fe/AlGaAs Schottky contact and an Fe/Al2O3 barrier. Both types of structures are formed in situ using a multichamber molecular-beam epitaxy system. A detailed analysis of the transport data confirms that tunneling occurs in each case. We find that the spin polarization achieved in the GaAs using the Al2O3 barrier is 40% (best case; 30% typical), but the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
89
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 14 publications
1
89
1
1
Order By: Relevance
“…3 This explains the large amount of work on spintronics with hybrid metal/semiconductor heterostructures for the past ten years, once it was proposed to solve the problem of impedance mismatch 4 by the use of an interface resistance, typically a tunneling barrier. [5][6][7] Various experiments have been performed to detect by electrical (e.g., the electrical Hanle effect) or by optical means a spin-polarized current injected from a ferromagnetic reservoir into a III-V semiconductor through an Al 2 O 3 barrier, [8][9][10][11][12] through MgO, [12][13][14][15][16] and through GaO, 17 or into Si through Al 2 O 3 (Refs. [18][19][20][21][22] and SiO 2 (Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 This explains the large amount of work on spintronics with hybrid metal/semiconductor heterostructures for the past ten years, once it was proposed to solve the problem of impedance mismatch 4 by the use of an interface resistance, typically a tunneling barrier. [5][6][7] Various experiments have been performed to detect by electrical (e.g., the electrical Hanle effect) or by optical means a spin-polarized current injected from a ferromagnetic reservoir into a III-V semiconductor through an Al 2 O 3 barrier, [8][9][10][11][12] through MgO, [12][13][14][15][16] and through GaO, 17 or into Si through Al 2 O 3 (Refs. [18][19][20][21][22] and SiO 2 (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] as well as into Ge through MgO. [26][27][28][29][30][31][32][33][34] Among the latest experiments, the transformation of a spin-polarized electron current into left-or righthanded circularly polarized light in a spin light-emitting diode (spin LED) integrating a III-V semiconductor heterostructure 8,11,[13][14][15][16][17]19,23,34,35 is one of the most striking physical phenomena. The electric dipolar selection rules involved in a quantum well 36 (QW) embedded in a spin LED during electron-hole recombination require spin injection with an out-of-plane magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…A tunnel barrier provides a readily implemented post-growth contact that alleviates the large mismatch in conductivity between the metal and semiconductor that would otherwise preclude spin injection 14,15 . Similar Fe/Al 2 O 3 contacts were deposited directly on n-Si(001) wafers to provide reference samples for analysis of the transport process using procedures described previously on the basis of the Rowell criteria 13,16 . These measurements confirmed that transport at low temperatures occurred by tunnelling.…”
mentioning
confidence: 99%
“…Second, Si epilayers (n-doped, 80 nm thick) were grown on n-Al 0.1 Ga 0.9 As/GaAs/p-Al 0.3 Ga 0.7 As quantum-well structures, which were grown in turn on p-GaAs(001) substrates in a stand-alone MBE chamber. Although the crystalline quality of the Si is lower and a further heterointerface is introduced (Si/Al 0.1 Ga 0.9 As), these samples enable a quantitative determination of the electron spin polarization of the electrons that radiatively recombine in the GaAs through standard analysis using quantum selection rules 12 .The Fe/Al 2 O 3 contacts were deposited in a separate MBE system (see the Methods section) 13 . A tunnel barrier provides a readily implemented post-growth contact that alleviates the large mismatch in conductivity between the metal and semiconductor that would otherwise preclude spin injection 14,15…”
mentioning
confidence: 99%
See 1 more Smart Citation